Putin, V.V. 100 and 1 More Quotations / Comp. by S.M. Khenkin, I.A. Istomin, S.M. Kretov [and oth.]. Moscow: Prospekt, 2017. 192 p. (in Russian) (Сравнительная политика)
Putin, V.V. 100 and 1 More Quotations / Comp. by S.M. Khenkin, I.A. Istomin, S.M. Kretov [and oth.]. Moscow: Prospekt, 2017. 192 p. (in Russian).